2023
DOI: 10.3390/agriculture13040786
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Feed Additive for the Prevention of Clostridial Disease in High-Yielding Dairy Cattle

Abstract: The purpose of this research is to develop and test a new approach to prevent clostridial disease in cattle, based on the use of a new compound biologically active feed additive (BFA). Some properties of the separate components of BFA are characterized. The research showed that a strain of the bacterium Bacillus amyloliquefaciens159 has an expressed antagonism to toxin-producing strains of C. perfringens. When using the test strains of C. perfringens from the ATCC collection (13124 as type A, 10543 as type C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Feeding a mixture of L. animalis LA-51 and P. freudenreichii PF-24 to Holstein calves supported the development of intestinal cells during the pre-weaning period [2]. Lastly, it is noteworthy to mention that the support of the health of the host against C. perfringens serotypes cannot solely rely on vaccination, as it has been demonstrated that only 40-50% of vaccinated lactating dairy cows develop an effective memory against this pathogen [32]. This can be even more critical if we consider that newborn calves do not have a developed immune system from a systemic or gut-located standpoint [33] and are not vaccinated early in life, meaning that they are at high risk if they encounter C. perfringens.…”
Section: Discussionmentioning
confidence: 93%
“…Feeding a mixture of L. animalis LA-51 and P. freudenreichii PF-24 to Holstein calves supported the development of intestinal cells during the pre-weaning period [2]. Lastly, it is noteworthy to mention that the support of the health of the host against C. perfringens serotypes cannot solely rely on vaccination, as it has been demonstrated that only 40-50% of vaccinated lactating dairy cows develop an effective memory against this pathogen [32]. This can be even more critical if we consider that newborn calves do not have a developed immune system from a systemic or gut-located standpoint [33] and are not vaccinated early in life, meaning that they are at high risk if they encounter C. perfringens.…”
Section: Discussionmentioning
confidence: 93%
“… 61 Good hygiene practices, feeding management, and vaccination can prevent the infection caused by C. perfringens . 4 , 62 Preventive strategies for pathogens depend on good farm management practices, limiting their susceptibility to infection through vaccination, high hygienic levels of tools and structures for handling of the animal can avoid risk of infections ( Table 1 ). Good management practices in harvesting, storing, and feeding the animals prevent diseases associated with enterotoxic clostridia.…”
Section: Common Causes Of Bacterial Infections In Dairy Calvesmentioning
confidence: 99%
“…With increased vascular permeability, extravasation of fluids and proteins occurs into the perivascular space, with consequent edema. When it occurs in brain tissue, it is called eosinophilic proteinaceous perivascular edema or microangiopathy [40][41][42][43][44].…”
Section: Enterotoxemiasmentioning
confidence: 99%
“…There are also different PCR techniques that, despite not directly detecting the toxin(s) produced by C. perfringens types A-E, but rather the genes that encode their production, allow the typification of the C. perfringens involved in a particular case or outbreak. Although the presence of toxins in intestinal contents is the most important indicator of enterotoxemia, it is necessary to combine this finding with others, especially the history of the animal and the property, clinical signs, necropsy findings and histopathology of the injured organs [40][41][42][43].…”
Section: Enterotoxemiasmentioning
confidence: 99%